Emotional logic development profiles – validating the benefits and safety of emotional logic training. (2nd July 2016) - Zahra, Daniel; Langsford, Marian; Griffiths, Trevor
Abstract: Objective : Validation of the Emotional Logic Development Profile (ELDP) as a measure of improvements in emotional literacy and well-being resulting from emotional logic (EL) training; a programme designed to improve emotional literacy and reduce depression and anxiety. Method : A general adult population sample was recruited to obtain normative ELDP data, from which clinically significant change, reliability and psychometric properties could be assessed against a patient sample. This consisted of 53 patients at a UK primary care medical practice who were offered EL while on a waiting list for other psychological therapies. Patients completed the PHQ-9, GAD-7 and ELDP at initial and two-month follow-up sessions. ELDP factor structure and sensitivity were assessed, and semistructured follow-up interviews provided additional qualitative data on acceptability. Results : PHQ-9, GAD-7 and ELDP all showed significant improvements between pre- and post-EL measurement. The ELDP appears unidimensional, provides additional information to the PHQ-9 and GAD-7 and is sensitive to change. Furthermore, 17% of patients showed reliable, clinically significant improvements in ELDP scores. General practice (GP) consultations and medication use both significantly reduced. Conclusions : The ELDP reliably measures ELs impact on reducing depression and anxiety. Further evaluation of EL viability for wider use in primary care, and in other age groups, may prove beneficial.